Reimagining historically Black colleges and universities : survival beyond 2021 - Crosby, Gary B.; White, Khalid; Chanay, Marcus A.; Hilton, Adriel A. (Emerald Publishing Limited, 2021)
The Nation's Historically Black Colleges and Universities (HBCUs) are more relevant today than ever before. As the national student loan debt grows, as the racial wealth gap continues to widen and as unemployment in the African American community continues to exceed that of other racial demographic groups, the HBCUs represent a collective means to combating socioeconomic ills. The HBCUs stand in the gap; supporting the African American community at-large. Through the use of best practices and HBCU administrative experiences, the authors offer a path forward for avoiding political and cultural missteps. They tout the rich tradition, legacy, as well as outcomes of HBCUs. New contributions to the field are made through a collective of higher education professionals and change agents whom are tied to HBCU scholarship. A relevant and practical book for HBCU leadership and administrators, HBCU faculty leaders and researchers that want to uncover the ways and means for cultivating success within the HBCUs longitudinally. New contributions to the field are made through a collective of higher education professionals and change agents who are tied to HBCU scholarship.
Includes index.
Keywords: African American universities and colleges.; Education -- Higher.; Higher & further education, tertiary education.; elektronické knihy; electronic books